Preparation, fabrication and biocompatibility of novel injectable temperature-sensitive chitosan/glycerophosphate/collagen hydrogels. - Song, K; Qiao, M; Liu, T; Jiang, B; Macedo, H; Ma, X; Cui, Z (2010)
This paper introduces a novel type of injectable temperature-sensitive chitosan/glycerophosphate/collagen (C/GP/Co) hydrogel that possesses great biocompatibility for the culture of adipose tissue-derived stem cells. The C/GP/Co hydrogel is prepared by mixing 2.2% (v/v) chitosan with 50% (w/w) β-glycerophosphate at different proportions and afterwards adding 2 mg/ml of collagen. The gelation time of the prepared solution at 37°C was found to be of around 12 min. The inner structure of the hydrogel presented a porous spongy structure, as observed by scanning electron microscopy. Moreover, the osmolality of the medium in contact with the hydrogel was in the range of 310-330 mmol kg(-1). These analyses have shown that the C/GP/Co hydrogels are structurally feasible for cell culture, while their biocompatibility was further examined. Human adipose tissue-derived stem cells (ADSCs) were seeded into the developed C/GP and C/GP/Co hydrogels (The ratios of C/GP and C/GP/Co were 5:1 and 5:1:6, respectively), and the cellular growth was periodically observed under an inverted microscope. The proliferation of ADSCs was detected using cck-8 kits, while cell apoptosis was determined by a Live/Dead Viability/Cytotoxicity kit. After 7 days of culture, cells within the C/GP/Co hydrogels displayed a typical adherent cell morphology and good proliferation with very high cellular viability. It was thus demonstrated that the novel C/GP/Co hydrogel herein described possess excellent cellular compatibility, representing a new alternative as a scaffold for tissue engineering, with the added advantage of being a gel at the body's temperature that turns liquid at room temperature.